A global analysis of bank profitability factors - Prosper Lamothe; Enrique Delgado; Miguel A. Solano; Sergio M. Fernández (Humanities & Social Sciences Communications, 2024)
Abstract We analyze the factors that explain banks’ profitability globally and by region. With increasing globalization, knowing the different aspects of bank profitability is essential for countries’ financial stability and economic growth. This study used a sample of 2,091 commercial banks operating in 110 countries grouped into major world regions. With random effect regression models, the global results show that the internal factors that explain the bank´s profitability are listed entities, impaired loans, efficiency, gross interest margin, and capitalization. For its part, the most significant external factors are related to the position of the countries in the ranking by assets, inflation, unemployment, interest rates, and economic growth. From a regional perspective, the results allow us to deduce with high robustness the existence of variable sets that determine bank profitability in each region and that regional models outperform global models in most cases.